Removal of heavy metal from aqueous solution by apple residues / Norliati Mohamed Nakman - Mohamed Nakman, Norliati (Faculty of Applied Sciences, 2010)
This study is carried out to investigate the ability of apple residues to remove heavy metal from aqueous solution. Apple residues are considered as one of the agricultural wastes can be used as adsorbents. The optimum condition in the removal of lead, cadmium and chromium by apple residues was studied by varying all parameters which affect the biosorption of apple residues on heavy metals. These include optimum pH of biosorption, effect of adsorbent dosage and effect of initial metal concentration. The sample then was analyze using Atomic Absorption Spectrometer.